2016
DOI: 10.18632/aging.100912
|View full text |Cite
|
Sign up to set email alerts
|

Centenarians’ offspring as a model of healthy aging: a reappraisal of the data on Italian subjects and a comprehensive overview

Abstract: Within the scenario of an increasing life expectancy worldwide it is mandatory to identify determinants of healthy aging. Centenarian offspring (CO) is one of the most informative model to identify trajectories of healthy aging and their determinants (genetic and environmental), being representative of elderly in their 70th whose lifestyle can be still modified to attain a better health. This study is the first comprehensive investigation of the health status of 267 CO (mean age: 70.2 years) and adopts the inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
3
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 70 publications
3
47
3
2
Order By: Relevance
“…Several previous studies have found that individuals with long-lived parents tend to age healthier [3,29]. Parental longevity influences aging not only because of genetics, but also because of shared lifestyle and environmental factors [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have found that individuals with long-lived parents tend to age healthier [3,29]. Parental longevity influences aging not only because of genetics, but also because of shared lifestyle and environmental factors [3].…”
Section: Discussionmentioning
confidence: 99%
“…Body weight and height were self-reported. In order to define BMI categories, cut-off points proposed by the Official Mexican Regulation to treat obesity and overweight (NOM-008-SSA3-2017) in adults aged 60 years or older and by the Social Security in Mexico to evaluate and treat the nutritional status of adults aged 60 years or older, were used and are as follows: underweight (< 22), normal weight (22)(23)(24)(25)(26)(27), overweight (27)(28)(29)(30) and obese (> 30) [17,18]. We define drinking categories according to the NIAAA: "for women, low-risk drinking is defined as no more than 3 drinks on any single day and no more than 7 drinks per week.…”
Section: Study Variablesmentioning
confidence: 99%
“…Square: male, circle: female, diamond: both genders are possible. urinary tract infections (6.7%); urge incontinence, catheter (6.2%); prostate hypertrophy benign (with/without surgery) (4.8%); neurological/psychiatric disease (15.8%) epilepsy, insomnia, migraine (5.3%); balance problems, dizziness (3.8%); depression, loneliness (2.9%); delirium after infection or fracture (1.9%); Parkinson's disease (1.9%), starting cognitive decline (1.9%); gastrointestinal (14.8%) kidney stones (removed), renal failure (6.7%); diverticulitis, (bleeding) ulcers, polyps, stomach bleeds, appendectomy (5.7%); resection gall bladder, removal gall stones (2.4%); lung disease (10.5%) pneumonia (5.3%); COPD (5.3%); Other erysipelas, chronic leg ulcer, pericarditis (4.3%); hysterectomy, prolapse, cysts removal (4.3%); cholesteatoma (0.5%); anemia (1.0%); restless legs (1.0%); (48,88,19) 119 (11,102,6)…”
Section: Fig 3 Data Collection From Centenarians and Their Family--mmentioning
confidence: 99%
“…Indeed, results from the New England Centenarians Study indicated that siblings from centenarians are ~8--12 times more likely to reach 100 years compared to individuals with no centenarian siblings [18]. Children of centenarians also profit from Holstege et al, the advantage they inherited by their centenarian parent: they live longer, and have almost 90% lower risk of developing myocardial infarction, stroke and diabetes compared to age--matched peers whose parents have average life spans [16,19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation